2012
DOI: 10.1007/s13762-012-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation and field application of tailor-made nitrogen dioxide passive samplers

Abstract: This study describes the validation and field application of new tailor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The Indoor and outdoor NO 2 levels were collected by lab made passive samplers [15] in order to estimate NO 2 levels emitted from different sources. The major source of NO 2 outdoors was traffic emissions, while the burning of incense was the primary indoor source.…”
Section: No 2 Samplingmentioning
confidence: 99%
“…The Indoor and outdoor NO 2 levels were collected by lab made passive samplers [15] in order to estimate NO 2 levels emitted from different sources. The major source of NO 2 outdoors was traffic emissions, while the burning of incense was the primary indoor source.…”
Section: No 2 Samplingmentioning
confidence: 99%
“…Saenz-de-Miera and Rosselló [13] observed a 1 % tourist increase in Mallorca related to a 0.45 % increase in PM 10 concentration. Nitrogen dioxide concentration in Chiang Mai and Nakhon Si Thammarat's tourist cities were comparable in the range 13 to 96 µg m -3 , while the concentration in Seoul, Korea ranged 41 -181 µg m -3 [14][15][16]. Results indicated that NO 2 levels in tourist cities were influenced by factors such as tourism and other anthropogenic activities.…”
Section: Introductionmentioning
confidence: 88%
“…The concentrations of the reagents should be such that, on mixing, the ratio of the two reagents in the extraction solution are 7 × 10 −3 g of NEDD per 1 g of sulphanilamide with absolute reagent amounts per sample PDT of the order of 0.42 mg and 60 mg, respectively. The colour absorption should be measured within 2 h. As part of a general evaluation of custom-built tube-like passive samplers for NO 2 , Bootdee et al [24] Equation (1) that is used to calculate the exposure-average NO 2 concentration is based on Fick's first law of diffusion with an assumption of a time-independent linear concentration profile of NO 2 along the tube. Bias in the derived NO 2 occurs when this assumption breaks down.…”
Section: Appendix A2 Bias In Quantification Of Absorbed Nitritementioning
confidence: 99%
“…Two further field studies involving custom-built tube-like passive samplers for NO 2 provide some information relevant to meteorology-associated biases in field deployments. A study by Bootdee et al [24] exposed three geometries of tube (a polyethylene tube 5.4 cm long, 1.4 cm i.d. ; and two sizes of polypropylene tube, 5.3 cm long, 1.3 cm i.d.…”
Section: Field Studiesmentioning
confidence: 99%